THU0469 CLUES TO RECOGNIZE SECONDARY FIBROMYALGIA IN PATIENTS WITH OSTEOARTHRITIS ACCORDING TO A FIBROMYALGIA ASSESSMENT SCREENING TOOL OF SCALES ON A MULTIDIMENSIONAL HEALTH ASSESSMENT QUESTIONNAIRE (MDHAQ/FAST3-F). (June 2019) - Riad, Mariam; Castrejon, Isabel; Block, Joel; Pincus, Theodore
Abstract : Background: A multidimensional health assessment questionnaire (MDHAQ) includes scales for a self-report painful joint count, symptom checklist, and fatigue visual analog scale (VAS), which may be compiled into a fibromyalgia assessment screening tool (FAST3-F), in addition to physical function, pain VAS, and patient global VAS, compiled into routine assessment of patient index data (RAPID3). FAST3-F agrees >80% with 2011 formal fibromyalgia (FM) criteria in rheumatoid arthritis (RA) patients who have secondary FM. Objectives: To recognize clues to secondary FM in osteoarthritis (OA) patients seen in routine care, according to FAST3-F, and to analyze MDHAQ demographic and other clinical data in OA patients who did or did not meet MDHAQ/FAST3-F criteria for secondary FM. Methods: All patients complete an MDHAQ at all visits prior to seeing the rheumatologist at an academic rheumatology site. The 2-page MDHAQ includes RAPID3 to analyze clinical status, and a cumulative 0–3 FAST3-F scale to recognize FM, FAST3-F is scored 0-3, with 1 point each for 0-10 fatigue VAS ≥6, 0-54 self-report joint count ≥16, and 0-60 symptom checklist ≥16. FAST3-F scores of ≥2/3 agree >80% with formal 2011 FM revised diagnostic criteria, based on data for area under the curve (AUC) on receiver operator characteristic (ROC) curves. A two-sample t test was used to compare the two groups; p values were considered significant if ≤0.05. Results: Among 173 OA patients, 55 (32%) met FAST3–F criteria of ≥2/3 for secondary FM. Patients who met criteria had lower formal educational level (p=0.01-Table), but did not differ significantly from those who did not meet criteria according to age, sex, or body mass index (BMI) (Table). MDHAQ scores for physical function, pain, patient global assessment, RAPID3, poor sleep quality, anxiety, and depression were significantly higher in the FAST3-F positive than negative patients (p<0.001-Table). Abbreviations: FAST3-F= fibromyalgia assessment screening tool, BMI=body mass index Conclusion: MDHAQ/FAST3-F provides clues to identify OA patients with secondary FM in routine care. Nonetheless a definitive diagnosis requires a physician. The findings may be useful to recognize a basis for poor responses in clinical care, clinical trials, and other clinical research, and enhance understanding of pain mechanisms in OA versus FM versus OA with FM. Disclosure of Interests:  : None declared